Evolution of architectural graphics in the historical context (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article explores the dynamics and transformation of visualization methods in architectural graphics at different stages of history. The aim of research lies in the analysis of the evolution of these methods in historical development and their influx into current practice. This research is based on a review of the literature and analysis of the historical data and current trends in architectural graphics. The various stages in the development of methods for creating visual images in architectural graphics are examined, starting from traditional manual techniques and up to modern digital tools. It was found out that the training of architects in the period of antiquity and the Middle Ages was carried out orally, followed by the development of the method of building an object directly in practice. That is, the architect was personally involved from the creation of the idea to the construction of the object. It was mentioned that during the Renaissance, the workshop system of architectural education continued to study new theories and methods of depicting architectural graphics. Factors have been identified that influence the evolution of these methods: technological progress, cultural and social changes, and others.The article states that one of the professional benefits of architectural practice is the development of the author’s handwriting or graphic language, which is used to identify the author of the project, architect, or organization. We want to point out the best visual presentation of projects of architectural bureaus. It is seen that modern graphic language is diverse and a mix of traditional and modern visual techniques. It has been established that the evolution of methods for creating visual images in architectural graphics is rich in aspects and dynamic. The prospects for further research are also highlighted, including an analysis of the influx of digital technologies, the aesthetic aspects of visual communication, and the synthesis of traditional and current approaches. Recognize the need for further research for a deeper understanding of the evolution of architectural graphics and the development of innovative approaches to the creation of visual images.
Keywords: architectural graphics; author's handwriting; method of creating an architectural image; graphic visualization of an object; graphic style; master craftsmen; architectural bureau